A Comparative Study of Exegesis in Al-Munir Fi Al-Aqidah Wa Al-Syari’ah Wa Al-Manhaj and Tafsir Al-Mizan Fi Tafsir Al-Qur’an Regarding Leadership Verses - Permana, Asep Amar; Zulaiha, Eni (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2024)
The purpose of this writing is to explore the school of exegesis and the comparative interpretation of leadership verses in Al-Munir Fi Al-Aqidah Wa Al-Syari’ah Wa Al-Manhaj and Tafsir Al-Mizan Fi Tafsir Al-Qur’an. The research method employed in this writing is qualitative and analytical-descriptive. The initial step in this research is to trace the Quranic verses related to leadership in both exegeses. Then, a comparison is made between their interpretations, and the differences in their exegesis schools are analyzed. It was found in this study that the exegesis school of Al-Munir Fi Al-Aqidah Wa Al-Syari’ah Wa Al-Manhaj tends towards the Sunnah interpretation, using the tahlili method, employing a combined approach of exegesis between bi al-ma’tsur and bi ar-ra’y which has a literary, social, and fiqh-oriented interpretation style. Meanwhile, Tafsir Al-Mizan Fi Tafsir Al-Qur’an represents the Shia interpretation, utilizing the tahlili method and heavily relying on its sources, which have a theological or philosophical orientation. In interpreting leadership verses in both exegeses, the author found one such verse in Surah An-Nisa [4]: 58-59, which is one of the Sunnah leadership verses regarding trustworthiness in leadership, and in Surah Al-Maidah [5]: 67, which is one of the well-known Shia leadership verses concerning propagation.